An incremental algorithm for maintaining the dominator tree of a reducible flowgraph - Ramalingam, G.; Reps, Thomas (Proceeding POPL '94 Proceedings of the 21st ACM SIGPLAN-SIGACT symposium on Principles of programming languages, 1994)
We present a new incremental algorithm for the problem of maintaining the dominator tree of a reducible flowgraph as the flowgraph undergoes changes such as the insertion and deletion of edges. Such an algorithm has applications in incremental dataflow analysis and incremental compilation.